The economic benefits of Tindahan ni Gloria Labandera (Coconut Farmers Food Access Program) on the Poorest Barangays in Aklan - Young, Erna T.
This research study ams to asses the Tindahan ni Gloria Labandera (TGL) Programs on its program-component the CFFAP in the two poorest barangays in Aklan- Brgy.Bugtong Bato in Ibajay and Brgy. Dapdap in Tangalan. Specifically, it aims to monitor and assess the two barangays in terms of its economic benefits received from TGL in terms of basic commodities, price, quality and savings generated from the purchase and to identify the issues/concenrs and the recommendations to address these issues/concerns. There are eight basic commodities sold to the respondents of Brgy. Bugtong Bato and Brgy Dapdaap, namely: rice, cooking oil, noodles, sardines, coffee, sugar, milk and laundry soap. These commodities were offered at a low price compared to the prices of stores in the vicinity. The effects of TGL in terms of basic commodities drew high patronage especially for rice at 87% and lowest for laundry soap at 10%. In terms of price, TGL was generally low compared to other stores in the vicinity. While in terms of quality and savings, the respondents' assessments were good at 55%; and savings were at â‚±15.09 for its daily purchase of the 8 commodities. The economic benefits of the CFFAP from TGL were: right quality and weight of goods; savings from purchase; saving from fare to the poblacion and to its time and effort, the fact that the poblacion was far from the 2 barangays. The issues/concerns of the study were: some of the basic commodities were not available sometimes and there were commodities which were wanted to be bought from TGL. The problem fell in the incomplete lines of basic commodities and not made available always during times of need. Looking into the findings of the gathered data from the survey-questionnaire, low prices of prime commodities is an urgent need of Brgy. Bugtong Bato and Brgy Dapdap. However, these prices will not find meaning in the economy of these two barangays if TGL cannot improve its services like for example: increasing the supply of these prime commodities, to be able to provide the purchasing need of every family; and be made available for each purchase anytime the need arises for the commodities. Also, eight basic commodities are not enough to alleviate the needs of a poor family. The respondents though, have been explicit for more commodity-needs. The first five are: OC medicines, school supplies, bath and laundry soap, iodized salt, and sanitary napkin for women. The following are the recommendations of the study: Improve the services of TGL by increasing its supply of prime commodities to meet every purchasing need; These basic commodities must be made available always for the purchasing need of every consumer. And a bigger store for TGL is necessary to be able to carry all the items needed by a poor consumer and also provide them with more choices for a brand name of a product needed.